PERANCANGAN ARSITEKTUR ENTERPRISE MENGGUNAKAN FRAMEWORK TOGAF (STUDI KASUS PT XYZ) - Kezaldo Kezaldo (Institut Bisnis Muhammadiyah Bekasi, 2020)
It is undeniable that Covid-19 has indiscriminately stopped activities in various sectors. From the government sector to the business and education sectors. Various efforts have been made by both the government and the company to survive in the Covid-19 period, such as create rules of working from home. However, the existing regulations need good architectural support so that every activity can run well. Through this journal the writer tries to explore architectural changes that can support each activity with the concept of 50% office capacity and working from home with the TOGAF approach. Due to the wide scope of activities, this research is limited to system architecture with activities oil trading at the head office which can later become blueprints for other divisions.